Ginkgo biloba extract (Egb761) attenuates zinc-induced tau phosphorylation at Ser262 by regulating GSK3β activity in rat primary cortical neurons1. Issue 6 (10th June 2015) - Kwon, Kyoung Ja; Lee, Eun Joo; Cho, Kyu Suk; Cho, Du-Hyong; Shin, Chan Young; Han, Seol-Heui
<x xml:space="preserve">Abstract</x> Egb761 attenuates zinc-induced tau hyperphosphorylation at Ser262 and inhibits GSK3beta (Ser9) phosphorylation ROS-dependently and -independently.